Effects of obesity on weight‐bearing versus weight‐supported exercise testing in patients with COPD. Issue 3 (9th December 2015) - Maatman, Robbert C.; Spruit, Martijn A.; van Melick, Paula P.; Peeters, Jos P.I.; Rutten, Erica P.A.; Vanfleteren, Lowie E.G.W.; Wouters, Emiel F.M.; Franssen, Frits M.E.
Abstract: Background and objective: Obesity is associated with increased dyspnoea and reduced health status in patients with chronic obstructive pulmonary disease (COPD). Studies on the effects of obesity on exercise capacity showed divergent results. The objective of this study is to investigate the impact of obesity on weight‐bearing versus weight‐supported exercise tolerance in obese and normal weight patients, matched for age, gender and degree of airflow limitation. Methods: Retrospective analyses of data obtained during pre‐pulmonary rehabilitation assessment in 108 obese COPD patients (OB) (age: 61.2 ± 5.3y, FEV1 : 43.2 ± 7.4%, BMI: 34.1 ± 3.9 kg/m 2, ) and 108 age and FEV1 ‐matched normal weight COPD patients (NW) (age: 61.7 ± 3.6y, FEV1 : 41.5 ± 8.4%, BMI: 22.9 ± 1.2 kg/m 2, ). Cardiopulmonary exercise test (CPET) and 6 min walk test (6MWT) were performed, Borg scores for dyspnoea and leg fatigue were recorded, before and after the tests. Results: Six‐minute walk distance differed between OB (398 ± 107 m) and NW patients (446 ± 109 m, P  < 0.05), while peak cycling exercise load was comparable (OB: 75 ± 29 W, NW: 70 ± 25 W, ns). Dyspnoea (OB 3.2 ± 2.0 vs NW 3.1 ± 1.7, ns) and leg fatigue (OB 2.4 ± 2.3 vs NW 1.9 ± 1.7, ns) were not significantly different in OB compared with NW after 6MWT, or after CPET (dyspnoea: OB 5.1 ± 2.4 vs NW 5.4 ± 2.2, ns; leg fatigue: OB 4.0 ± 2.3 vs NW 4.0 ± 2.7, ns). Conclusion: In contrast to weight‐supported exercise, obesity has a negative impact on weight‐bearing exercise capacity, despite comparable exercise‐related symptoms. The results of this study enhance the understanding of the impact of obesity on physical performance in COPD. Abstract : This study investigated the effects of weight‐supported versus weight‐bearing exercise in obese and normal weight COPD patients, matched for FEV1, age and gender. While weight‐bearing exercise capacity was reduced, weight‐supported exercise and symptoms were comparable between groups. Watch the video abstract